Intravenous Lipid Emulsions in Anticonvulsants' Toxicity - Simeonka Dimitrova; Stela Dragomanova; Gabriela Kehayova (MDPI AG, 2024)
In recent years, an innovative approach has emerged in the field of toxicology for managing acute intoxications caused by lipophilic substances: intravenous lipid emulsions (ILEs). Through numerous experiments and case reports, the efficacy of lipid emulsions in counteracting toxicities induced by lipophilic agents, including a significant number of antiepileptic (AE) drugs, have become increasingly evident. Data spanning a 10-year period (2010-2020) were analyzed by searching through multiple scientific publication platforms like PubMed, Science Direct, Research Gate, and Springer Link. This study focused on reviewing relevant case reports detailing successful intravenous lipid emulsion (ILE) administration in patients with acute intoxications with antiepileptics, specifically examining the impact of fat emulsions on neurological status, Glasgow Coma Scale (GCS) scores, and corrected QT interval concerning hemodynamic instability. The typical symptoms of antiepileptic toxicity include central nervous system depression, ataxia, and nystagmus. Intravenous lipid emulsion application resulted in an increase in Glasgow Coma Scale scores and enhanced recovery from drug intoxication. This study provides a comprehensive overview of the potential utility of ILE as a component to antidote therapy in cases of acute AE poisoning involving neurotropic drugs. The process involves the engagement of various mechanisms of antitoxic activity.